Multiple copies of eukaryotic translation initiation factors in Brassica rapa facilitate redundancy, enabling diversification through variation in splicing and broad‐spectrum virus resistance. (30th December 2013) - Nellist, Charlotte F.; Qian, Wei; Jenner, Carol E.; Moore, Jonathan D.; Zhang, Shujiang; Wang, Xiaowu; Briggs, William H.; Barker, Guy C.; Sun, Rifei; Walsh, John A.
Summary Recessive strain‐specific resistance to a number of plant viruses in the Potyvirus genus has been found to be based on mutations in the eukaryotic translation initiation factor 4E (eIF4E) and its isoform, eIF(iso)4E. We identified three copies of eIF(iso)4E in a number of Brassica rapa lines. Here we report broad‐spectrum resistance to the potyvirus Turnip mosaic virus (TuMV) due to a natural mechanism based on the mis‐splicing of the eIF(iso)4E allele in some TuMV‐resistant B. rapa var. pekinensis lines. Of the splice variants, the most common results in a stop codon in intron 1 and a much truncated, non‐functional protein. The existence of multiple copies has enabled redundancy in the host plant's translational machinery, resulting in diversification and emergence of the resistance. Deployment of the resistance is complicated by the presence of multiple copies of the gene. Our data suggest that in the B. rapa subspecies trilocularis, TuMV appears to be able to use copies of eIF(iso)4E at two loci. Transformation of different copies of eIF(iso)4E from a resistant B. rapa line into an eIF(iso)4E knockout line of Arabidopsis thaliana proved misleading because it showed that, when expressed ectopically, TuMV could use multiple copies which was not the case in the resistant B. rapa line. The inability of TuMV to access multiple copies of eIF(iso)4E in B. rapa and the broad spectrum of the resistance suggest it may be durable.